The circadian clock influences T cell responses to vaccination by regulating dendritic cell antigen processing - Mariana P. Cervantes-Silva; Richard G. Carroll; Mieszko M. Wilk; Diana Moreira; Cloe A. Payet; James R. O’Siorain; Shannon L. Cox; Lauren E. Fagan; Paula A. Klavina; Yan He; Tabea Drewinski; Alan McGinley; et al. (Nature Communications, 2022)
Circadian rhythms are known to impact a range of biological processes including in the immune system. Here the authors show how circadian rhythms modulate the T cell response to vaccination via regulation of dendritic cell metabolism.